(untitled) (Bangladesh Journal of Bioethics, 2018)
Intellectual property Rights (IPRs) is protected by different systems of laws. Journals must choose a definitive form of systems. Some Blackwell journals use copyright system and some Blackwell use license from authors. Now a days online journals are using creative common licenses. Under creative common license journals are open access, allowed to download, copy, distribute, and display derivative works with proper attribution to author or owner for noncommercial purpose at a free cost. Education on IPRs will support to comprehend ones rights, professional code of conduct and the doctrine of "fair use" in publication. One cannot do anything with once writing. Researchers, academic, editors and readers must have the basic knowledge on who owns the rights in a publication and what users can do with the publication by law.